Assessment of genetic integrity, splenic phagocytosis and cell death potential of (Z)-4-((1,5-dimethyl-3-oxo-2-phenyl-2,3dihydro-1H-pyrazol-4-yl) amino)-4-oxobut-2-enoic acid and its effect when combined with commercial chemotherapeutics - Rodrigo Juliano Oliveira (Genetics and Molecular Biology, 2018)
Abstract The increased incidence of cancer and its high treatment costs have encouraged the search for new compounds to be used in adjuvant therapies for this disease. This study discloses the synthesis of (Z)-4-((1,5-dimethyl-3-oxo-2-phenyl-2,3dihydro-1H-pyrazol-4-yl) amino)-4-oxobut-2-enoic acid (IR-01) and evaluates not only the action of this compound on genetic integrity, increase in splenic phagocytosis and induction of cell death but also its effects in combination with the commercial chemotherapeutic agents doxorubicin, cisplatin and cyclophosphamide. IR-01 was designed and synthesized based on two multifunctionalyzed structural fragments: 4-aminoantipyrine, an active dipyrone metabolite, described as an antioxidant and anti-inflammatory agent; and the pharmacophore fragment 1,4-dioxo-2-butenyl, a cytotoxic agent. The results indicated that IR-01 is an effective chemoprotector because it can prevent clastogenic and/or aneugenic damage, has good potential to prevent genomic damage, can increase splenic phagocytosis and lymphocyte frequency and induces cell death. However, its use as an adjuvant in combination with chemotherapy is discouraged since IR-01 interferes in the effectiveness of the tested chemotherapeutic agents. This is a pioneer study as it demonstrates the chemopreventive effects of IR-01, which may be associated with the higher antioxidant activity of the precursor structure of 4-aminoantipyrine over the effects of the 1,4-dioxo-2-butenyl fragment.